Safety and tolerability of antiepileptic drugs in women with epilepsy (literature review and own data) - K. Yu. Mukhin; O. A. Pylaeva; A. S. Petrukhin (Русский журнал детской неврологии)
Women with epilepsy are at particular risk of developing side effects due to antiepileptic drugs (AED). Neuroendocrine disorders in women can be caused by both epilepsy itself and the therapy. This literature review aims to evaluate safety and tolerability of different AED in girls and women of reproductive age, incidence of neuroendocrine disorders associated with AED, and pregnancy outcomes in women with epilepsy. We also provide some own research results. We conducted a retrospective analysis of data for 345female patients aged between 15 and 40 years that were followed up at the Svt. Luka’s Institute of Child Neurology and Epilepsy between 2000 and 2018. We also performed a separate analysis of neuroendocrine disorders and pregnancy outcomes in these women. We found that 65 patients (18.8 %) developed pronounced neuroendocrine reproductive and cosmetic disorders (menstrual disorders, including dysmenorrhea, opsomenorrhea, amenorrhea, anovulatory cycles, and infertility; cosmetic neuroendocrine disorders, including obesity, hirsutism, and hair loss; adverse pregnancy outcomes), which significantly reduced the quality of life. Neuroendocrine disorders were observed in 55patients, whereas adverse pregnancy outcomes were registered in 10 (14.2 %) out of 70pregnancies.Our findings suggest that the majority of women with epilepsy successfully gave birth to healthy children. The outcome of pregnancy depends on many factors, including the use of different AED. Valproic acid has the highest teratogenic potential. In our study, neuroendocrine reproductive disorders were primarily reported by women receiving valproic acid. Carbamazepines were the second most common AED associated with teratogenic effects and reproductive disorders. The most favorable results were observed in women receiving new AED, including oxcar- bazepine, topiramate, and levetiracetam.